Treatment of Disfiguring Cutaneous Lesions in Neurofibromatosis-1 with Everolimus: A Phase II, Open-Label, Single-Arm Trial - John M. Slopis; Octavio Arevalo; Cynthia S. Bell; Adelaide A. Hebert; Hope Northrup; Roy F. Riascos; Joshua A. Samuels; Keri C. Smith; Patti Tate; Mary Kay Koenig (Adis, Springer Healthcare, 2018)
Abstract Background Cutaneous neurofibromas cause disfigurement and discomfort in individuals with neurofibromatosis type 1 (NF-1). Methods The primary objective of this phase II, open-label, single-arm trial was to assess whether orally administered everolimus reduced the surface volume of cutaneous neurofibromas in patients with NF-1. Results Of 22 patients who took the study drug, 17 completed the trial; 5 patients withdrew due to adverse events. Sixteen patients had photographs of sufficient quality for assessment of the primary outcome. A significant reduction in lesion surface volume, defined as an end of trial volume > 2 standard errors (SE) less than baseline volume, was observed for 4/31 lesions (13%) from 3/16 patients (19%). Additionally, a statistically significant absolute change in average height for paired lesions was observed (p = 0.048). Although not a prespecified outcome measure, a dramatic reduction in the size of 3 large plexiform neurofibromas with a cutaneous component was also noted and documented by measurement of maximum circumference or magnetic resonance imaging-based volumetric analysis. Adverse events were common in this trial, but no serious adverse events occurred. Conclusions Although this was a small, exploratory trial that was not powered for significance, the reduction in surface volume observed in this study is noteworthy assuming that the natural course for untreated lesions is to maintain or increase in volume. Future studies are needed with larger study populations that incorporate longer durations of treatment and better standardization of volumetric measurements. Trial Registration ClinicalTrials.gov Identifier: NCT02332902